ASSESSMENT OF THE PROFITABILITY OF INNOVATIVELY ACTIVE ENTERPRISES OF UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The article proposes a methodology for assessing the profitability of innovatively active enterprises of Ukraine. The evaluation of the actual annual profit of the business using the indicator of economic added value (economic profit) is argued, since the accounting profit is not a qualitative characteristic of innovative development. An important remark in the context of this study is the assessment of innovative development, more specifically, the innovative activity of enterprises – in a relatively stable economic time that preceded the war in Ukraine. Because it is clear that a return to the previous indicators and surpassing them is possible only in a relatively stable economic environment. It remains obvious that the increase in the added value of products can be achieved by reducing the volume of intermediate consumption, with the help of improving integration processes, in the creation of chains of added value of products, renewal of production assets, scalability of enterprises, increasing the level of technical and technological equipment of Ukrainian enterprises. Proposals have been made regarding the general system of assessing the business value of innovatively active enterprises of Ukraine. This study is designed to outline the main prospects for the development of innovatively active enterprises of Ukraine. It is emphasized that for the analysis of the mutual influence of innovative activity and indicators of economic efficiency, it is worth applying more progressive indicators for profit, such as economic added value, market added value, managerial added value, a balanced system of indicators.
Keywords: innovative activity, profitability, efficiency, innovatively active enterprises, assessment, economic added value.